IMPLICATIONS OF RATIFICATION OF THE PARIS AGREEMENT ABOUT CLIMATE CHANGE FOR INDONESIA - Faidatul Makiyah; Danial Danial (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Climate change is a change caused either directly or indirectly by human activities that alter the composition of the atmosphere. One of these human activities is the use of fossil fuels. Paris Agreement is an international treaty with the main objective of addressing climate change through more inclusive and binding international cooperation for countries that ratify it.The author discusses: First, What are the Implications of Ratification Paris Agreement on Climate Change for Indonesia? Second, What is the Responsibility of the Indonesian Government in Controlling Carbon Emissions? reducing carbon emissions will be focused on the transportation and energy sectors.The author uses normative and empirical juridical methods, the research specifications used are descriptive analytical. The results of implications ratification Paris Agreement for Indonesia. First: ratification by Indonesia Paris Agreement is part of positive law in Indonesia and has implications for the emergence of obligations and rights. Second: It has implications for forming programs in the transportation and energy sectors. The government's responsibility in reducing carbon emissions has not yet had a significant effect on climate change. Although Paris Agreement encourages countries to achieve emission reduction targets, its implementation relies on voluntary action, no sanctions.